Therapeutic Anabolic and Anticatabolic Benefits of Natural Chinese Medicines for the Treatment of Osteoporosis - Jianbo He; Jianbo He; Jianbo He; Xiaojuan Li; Xiaojuan Li; Ziyi Wang; Samuel Bennett; Kai Chen; Zhifeng Xiao; Jiheng Zhan; Jiheng Zhan; Shudong Chen; et al. (Frontiers Media S.A., 2019)
Osteoporosis is a bone disease characterized by increasing osseous fragility and fracture due to the reduced bone mass and microstructural degradation. Primary pharmacological strategies for the treatment of osteoporosis, hormone replacement treatment (HRT), and alendronate therapies may produce adverse side-effects and may not be recommended for long-term usage. Some classic and bone-specific natural Chinese medicine are very popularly used to treat osteoporosis and bone fracture effectively in clinical with their potential value in bone growth and development, but with few adverse side-effects. Current evidence suggests that the treatments appear to improve bone metabolism and attenuate the osteoporotic imbalance between bone formation and bone resorption at a cellular level by promoting osteoblast activity and inhibiting the effects of osteoclasts. The valuable therapies might, therefore, provide an effective and safer alternative to primary pharmacological strategies. Therefore, the purpose of this article is to comprehensively review these classic and bone-specific drugs in natural Chinese medicines for the treatment of osteoporosis that had been deeply and definitely studied and reported with both bone formation and antiresorption effects, including Gynochthodes officinalis (F.C.How) Razafim. & B.Bremer (syn. Morinda officinalis F.C.How), Curculigo orchioides Gaertn., Psoralea corylifolia (L.) Medik Eucommia ulmoides Oliv., Dipsacus inermis Wall. (syn. Dipsacus asperoides C.Y.Cheng & T.M.Ai), Cibotium barometz (L.) J. Sm., Velvet Antler, Cistanche deserticola Ma, Cuscuta chinensis Lam., Cnidium monnieri (L.) Cusson, Epimedium brevicornum Maxim, Pueraria montana (Lour.) Merr. and Salvia miltiorrhiza Bunge., thus providing evidence for the potential use of alternative Chinese medicine therapies to effectively treat osteoporosis.